1)
2(a + 3) = -12
Divide by 2
a + 3 = -6
Subtract 3
a = -9
2)
3(p + 2) = 18
Divide by 3
p + 2 = 6
Subtract 2
p = 4
3)
4(2r + 8) = 88
Dive by 4
2r + 8 = 22
Subtract 8
2r = 14
Divide by 2
r = 7
4)
2(3a + 2) = -8
Divide by 2
3a + 2 = -4
Subtract 2
3a = -6
Divide by 3
a = -2
5)
4(k + 3) = 4
Divide by 4
k + 3 = 1
Subtract 3
k = -2
Answer:
Marry = $17
Ravi = $11
Alan = $34
Step-by-step explanation:
Let us assume
Mary be X
Ravi be Y
Alan be Z
So, the equation in total is
X + Y + Z = 62
It is given that
X = Y + 6
Z = 2X
Now we put the Z value in the total equation, so it would be
X + Y + 2X = 62
3X + Y = 62 .................................... (1)
And can we write
X = Y + 6
X - Y = 6 ................................. (2)
Now substitution these two equations,
3X + Y = 62
X - Y = 6
2X = 68
X = $17
So, Z = 2 × 17 = $34
And, Y
$17 + Y + $34 = $62
So, Y = $11
Answer:
The first blank: not equal
The 2nd blank: not right triangle (it's acute triangle)
The 3rd blank: equal
The 4th blank: it's right triangle
Step-by-step explanation:
4^2 = 3^2 + 3^2
<=> 16 = 9 + 9
<=> 16 = 18 ( nonsense)
so triangle LKJ is not right triangle
5^2 = 4^2 + 3^2
<=> 25 = 16 + 9
<=> 25 = 25 ( make sense)
so triangle ABC is right triangle
Done!! :))
12% of 1200 is 144, so subtract that. you get 1056. 12% of that is 126.72, so you subtract that. you get 929.28. 12% of that is 111.5136 and you subtract that. and so on and so forth. the answer would be 557.